Impact of Ramadan fasting on serum levels of major endocrinology hormonal and biochemical parameters in healthy non-athlete adults: A systematic review and meta-analyses. - Mohammad Poursalehian; Shahrzad Mohseni; Zhaleh Shadman; Mohammadreza Mohajeri-Tehrani; Rasha Atlasi; Mohsen Khoshniat Nikoo; Mostafa Qorbani; Bagher Larijani (PLoS ONE)
Background Ramadan Intermittent Fasting (RIF) has the potential to alter hormonal levels in the body. This study investigates the impact of RIF on hormonal levels among healthy individuals during Ramadan. Methods A systematic review and meta-analysis of previously published studies were conducted, focusing on healthy non-athlete adults. The intervention examined was Ramadan Intermittent Fasting, and the primary outcomes assessed were changes in endocrine hormonal and biochemical parameters. The pooled effect measure was expressed as odds ratio (OR) and 95% confidence interval (CI) using the random-effects model. Results A total of 35 original articles were retrieved, with a combined sample size of 1,107 participants eligible for the meta-analysis. No significant relationship was found between pre- and post-Ramadan hormonal levels of T3, T4, TSH, FT3, FT4, Testosterone, LH, FSH, Prolactin, PTH, Calcium, and Phosphorus (P-value<0.05). However, a substantial decrease in morning cortisol levels was observed across the studies (P-value: 0.08, Hedges' g = -2.14, 95% CI: -4.54, 0.27). Conclusions Ramadan Intermittent Fasting results in minimal hormonal changes and is a safe practice for healthy individuals. The fasting regimen appears to disrupt the circadian rhythm, leading to a decrease in morning cortisol levels.